The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4038/ss.v47i1.4701
|View full text |Cite
|
Sign up to set email alerts
|

Credit Intensity of Economic Growth – A Sectoral Analysis: Case of Sri Lanka

Abstract: This paper examines the dynamic relationship between credit and economic growth in Sri Lanka using aggregated and disaggregated data for the period [2003][2004][2005][2006][2007][2008][2009][2010][2011][2012][2013][2014][2015]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…This result confirms the 'demand following hypothesis, which emphasizes that economic growth tends to boost credit supply as elucidated by Robinson (1952), Kuznets (1955), andLucas (1988). This finding is consistent with previous studies that has determined that economic growth tends to enhance credit growth (Calza et al 2001;Cottarelli et al 2005;Perera, 2017). Inflation (INF) tends to be a negative determinant of credit growth as it is significant at 1 percent level in these estimates.…”
Section: Ardl Testsupporting
confidence: 91%
See 1 more Smart Citation
“…This result confirms the 'demand following hypothesis, which emphasizes that economic growth tends to boost credit supply as elucidated by Robinson (1952), Kuznets (1955), andLucas (1988). This finding is consistent with previous studies that has determined that economic growth tends to enhance credit growth (Calza et al 2001;Cottarelli et al 2005;Perera, 2017). Inflation (INF) tends to be a negative determinant of credit growth as it is significant at 1 percent level in these estimates.…”
Section: Ardl Testsupporting
confidence: 91%
“…However, a number of studies that addressed the economic impact of credit growth in general are available. For instance, Perera (2017) has conducted a sectoral analysis to find the impact of credit intensity on economic growth. The study has found evidence in support of the demand following hypothesis of finance-growth nexus.…”
Section: Empirical Evidence and Hypothesis Developmentmentioning
confidence: 99%
“…However, in this paper, using the VAR model, the main goal is to show exclusively dynamic responses of variables to unexpected shocks in other variables. Since the task of analysis in this paper is not to estimate the parameters per se but to observe the same dynamic responses, the variables of the subject VAR model are also non-stationary (e.g., Perera (2017), using non-stationary variables, as suggested by Sims (1980) and Sims, Stock and Watson (1990)). Therefore in further analysis raw data of variables are used.…”
Section: Var Modelmentioning
confidence: 99%
“…The progress of the economic sector can produce more abundant output so that the positive impact is the expansion of job opportunities and the high demand for goods/services. Some researchers have a positive influence such as (Abusharbeh, 2017;Alzyadat, 2021;Ananzeh, 2016;Korkmaz, 2015;Oni et al, 2014;Timsina & Pradhan, 2016) although the title of causality has not been determined (Perera, 2017).…”
Section: Introductionmentioning
confidence: 99%